THU0355 PARAMETRIC CARDIAC MAGNETIC RESONANCE IMAGING IDENTIFIES ARRHYTHMOGENIC SUBSTRATES IN SYSTEMIC SCLEROSIS PATIENTS. (13th June 2020) - Mavrogeni, S. I.; Gargani, L.; Pepe, A.; Monti, L.; Markousis-Mavrogenis, G.; De Santis, M.; Meloni, A.; Koutsogeorgopoulou, L.; Karabela, G.; Stavropoulos, E.; Katsifis, G.; Bratis, K.; et al.
Abstract : Background: Cardiac involvement in systemic sclerosis (SSc) accounts for 26-36% of deaths. This most frequently manifests as ventricular rhythm disturbances (VRDs), eventually culminating in sudden cardiac death. However, no specific guidelines exist for implantation of cardioverter defibrillators (ICD) in SSc patients. Parametric cardiovascular magnetic resonance (CMR) indices of myocardial oedema and fibrosis like native T1/T2 mapping have been shown to be associated with prognosis in SSc patients with acute cardiac events and normal echocardiograms. However, their relationship with arrhythmogenicity per se has not been previously investigated in SSc. Objectives: To investigate the relationship between parametric CMR indices and arrhythmogenicity in SSc patients. Methods: 84 consecutive SSc patients (80% diffuse-cutaneous SSc) from eight European centers presenting with cardiac symptoms were examined using a 1.5 T CMR system. 24h Holter recordings were obtained within a month of the CMR scan. The presence of VRDs was defined as any type of premature ventricular contraction (PVC) in couples, triplets, bigeminism, trigeminism, quadrigeminism and non-sustained ventricular tachycardia, as well as having >30 PVCs per hour. Logistic regression analysis was used to evaluate the relationship between VRD occurrence and native T1/T2 mapping as well as myocardial extracellular volume fraction (ECV). Results: Mean age in the cohort was 55 (13) years and 78 (93%) patients were female. Of these, 67 (80%) experienced at least one type of VRDs. Each 10 ms increase of native T1-mapping was associated with a higher occurrence of VRDs [odds ratio (95% confidence interval): 1.21 (1.08-1.36), p=0.001]. Similarly, a 1% increase in ECV conferred an increased probability of experiencing VRDs [1.25 (1.01-1.53), p=0.037]. Lastly, a 1ms unit increase in T2-mapping also led to increased probability of having experienced VRDs [1.09 (1.01-1.19), p=0.035]. Conclusion: Parametric CMR indices are associated with arrhythmogenicity in SSc patients with cardiac symptoms and should be investigated further in larger studies for their clinical utility in selecting high-risk SSc patients for ICD implantation. Disclosure of Interests: Sophie I. Mavrogeni: None declared, Luna Gargani: None declared, Alessia Pepe: None declared, Lorenzo Monti: None declared, George Markousis-Mavrogenis: None declared, Maria De Santis: None declared, Antonella Meloni: None declared, Loukia Koutsogeorgopoulou: None declared, Georgia Karabela: None declared, Efthymios Stavropoulos: None declared, Gkikas Katsifis Grant/research support from: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche, Consultant of: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche, Speakers bureau: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche, Konstantinos Bratis: None declared, Silvia Bellando Randone: None declared, Serena Guiducci: None declared, Cosimo Bruni: None declared, Alberto Moggi-Pignone: None declared, Theodoros Dimitroulas: None declared, Paraskevi Voulgari: None declared, Genovefa Kolovou: None declared, Vasiliki-Kalliopi Bournia Grant/research support from: Travel Grant from Boehringer Ingelheim, Monica Mukherjee: None declared, Joao Lima: None declared, George D. Kitas: None declared, Petros Sfikakis Grant/research support from: Grant/research support from Abvie, Novartis, MSD, Actelion, Amgen, Pfizer, Janssen Pharmaceutical, UCB, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim